Diskogenic microspurs as a major cause of intractable spontaneous intracranial hypotension. (20th September 2016) - Beck, Jürgen; Ulrich, Christian T.; Fung, Christian; Fichtner, Jens; Seidel, Kathleen; Fiechter, Michael; Hsieh, Kety; Murek, Michael; Bervini, David; Meier, Niklaus; Mono, Marie-Luise; Mordasini, Pasquale; et al.
Abstract : Objective: To visualize and treat spinal dural CSF leaks in all patients with intractable spontaneous intracranial hypotension (SIH) who underwent spinal microsurgical exploration. Methods: Patients presenting between February 2013 and July 2015 were included in this consecutive case series. The workup included spinal MRI without and with intrathecal contrast, dynamic myelography, postmyelography CT, and microsurgical exploration. Results: Of 69 consecutive patients, 15 had intractable symptoms. Systematic imaging revealed a suspicious single location of the leak in these 15 patients. Fourteen patients underwent microsurgical exploration; 1 patient refused surgery. Intraoperatively, including intradural exploration, we identified the cause of the CSF leaks as a longitudinal dural slit (6.1 ± 1.7 mm) on the ventral (10), lateral (3), or dorsal (1) aspect of the dura. In 10 patients (71%), a ventral, calcified microspur originating from the intervertebral disk perforated the dura like a knife. Three patients (22%) had a lateral dural tear with an associated spinal meningeal diverticulum, and in 1 patient (7%), a dorsal osteophyte was causal. The microspurs were removed and the dural slits sutured with immediate cessation of CSF leakage. Conclusion: The nature of the CSF leak is a circumscribed longitudinal slit at the ventral, lateral, or dorsal dura mater. An extradural pathology, diskogenic microspurs, was the single cause for all ventral CSF leaks. These findings challenge the notion that CSF leaks in SIH are idiopathic or due to a weak dura. Microsurgery is the treatment of choice in cases with intractable SIH.